EDUKASI DAN IMPLEMENTASI TEKNOLOGI TEST KIT KEBUNTINGAN SAPI POTONG UNTUK MENINGKATKAN EFISIENSI REPRODUKSI TERNAK PADA PETERNAKAN SAPI NUSA FAUNA PADANG - Syaiful, Ferry Lismanto; Agustin, Fauzia; Satria, Benny; Novia, Deni (Jurnal Hilirisasi IPTEKS, 2024)
Early pregnancy detection in beef cattle is a crucial aspect of reproductive management to enhance livestock reproductive efficiency. Delays in pregnancy detection can result in prolonged open days and reduced farm productivity. This activity aimed to educate and implement the use of a urine-based pregnancy test kit for beef cattle at Nusa Fauna Cattle Farm in Padang. The program was conducted at Nusa Fauna Cattle Farm, Pauh District, Padang City. The implementation methods included socialization, demonstration of test kit usage, and direct assistance in field application. The evaluation was conducted through interviews and questionnaires to assess the level of understanding and the effectiveness of test kit implementation in reproductive management. The results indicated increased farmers' knowledge, understanding, and skills in independently using the test kit. Before the education program, farmers relied on rectal palpation performed by veterinary personnel, which has limitations in detecting early-stage pregnancy. After the training, farmers were able to use the test kit independently. Implementing the test kit also facilitated faster pregnancy detection, allowing farmers to take strategic actions in livestock reproductive programs. This activity concludes that education and implementing pregnancy test kit technology can improve livestock reproductive efficiency by enabling earlier pregnancy detection. Applying this technology at the smallholder farming level can reduce open days and increase the success rate of artificial insemination (AI) in beef cattle.